Knowledge and Practice among Public Health Nurses in Disaster Response Phase - Putra, Ardia; Hajjul Kamil; Yuswardi, Yuswardi; Satria, Budi (Journal of Liaquat University of Medical & Health Sciences, 2022)
A disaster can be delineated as an occurrence that threatens and disrupts people’s lives and means of subsistence caused by natural, non-natural, and human factors, resulting in loss of life, environmental damage, loss of property, and psychological consequences. As a flexible profession that covers all conditions, nurses, particularly PHNs, are expected to be limited to providing care in the community and required to work in conditions of disaster emergency response. This literature review aims to identify the knowledge and perceived ability to practice of PHNs in the disaster emergency response phase. The study is based on a systematic review approach. The source of information for the present study derived from Internet-based literature, in the form of research results from online libraries at the local, national and international levels. Totally 43 references were used to establish this review study. The knowledge and perceived ability to practice PHNs in the disaster response phase will typically be identified in six viewpoints: warning, triage of disasters, saving and stabilizing lives, surveillance, risk communication, and technical skills. Therefore, handling situations among the alert and steady states is quite atypical; hence nurses must skillfully and technically deal with these conditions. KEYWORDS: Nurses, Public Health Nurses, Disaster Management, Disaster Nursing, Response Phase